Optimization and Antifungal Activity of Amide Analogues - Feng, Hui; Leng, Li; Liu, Jia; Tang, Yuanmou; Tang, Pengcheng; Zhang, Chixiang; Tang, Xioarong; Jiao, Shirong (Asian Journal of Chemistry, 2013)
Using salicylic acid as a lead compound, a series of its analogues (compounds 1-16) were designed and synthesized. Their activity of anti-pathogenic fungi of plants has been evaluated in the laboratory. The results showed that these compounds had certain antifungal activity against Sclerotinia sclerotiorum and Bipolaris maydis (Nisikado et Miyake) Shoem. Among them, the inhibition of growth for 2-(3-fluorophenylcarbamoyl)phenyl acetate (1) and 2-(3-chlorophenylcarbamoyl)phenyl acetate (2) reached 91.1 %, 92.8 % and 90.1 %, 90.1 % at a concentration of 100 mg L-1, respectively.